Studies on the Dynamics of Forms of Soil Iron in the Acid Soils of Kerala During Submergence - Harikumar K P (Department of Soil Science & Agricultural Chemistry, College of Agriculture, 1989)
The main objective of the study were to understand the pattern of distribution of water soluble, exchangeable, active free oxide, total amorphous, amorphous organic, amorphous inorganic and crystalline forms of iron and their variation under the influence of submergence, the effect of management practices on the variations in the available forms of iron under submergence and the relationship between soil reaction and the forms of iron in the major acid rice soils of Kerala. Viz., lateritic alluvium. Kari, kayal, karappadom, kole and pokkali. The pattern of distribution of different forms of iron studied, varied significantly among the six soils. The water soluble, exchangeable, active, free oxide, total amorphous and amorphous organic forms of iron were maximum in the kari soil, while crystalline iron was maximum in the lateritic alluvium. Kari and kole soils had the highest content of amorphous inorganic form of iron. The minimum content of water soluble iron was recorded in the kole and the lateritic alluvium, exchangeable and crystalline iron in karappadom soil, active, free oxide, total amorphous and amorphous inorganic forms of iron in pokkali soil and the amorphous organic iron in the lateritic alluvium. The total iron was highest in the kole and the lowest in the karappadom soils. Correlation studies indicated that pH had a significant negative correlation with water soluble and exchangeable forms of iron, while electrical conductivity, CEC, organic matter and clay content had positive correlation. Electrical conductivity and organic matter were positively correlated with active iron. Submergence significantly increased the pH and the contents of some of the forms of soil iron. Crystalline iron however, decreased with submergence. Active and free oxide forms of iron had no significant effect. The pH attained peak values on the 20th day of submergence in the lateritic alluvium, 30th day in the karappadom soil and 60th day in kayal, kole and pokkali soils. However, kari soil showed steady slow increases throughout the period of submergence. The addition of organic matter @ 5 t/ha and 2.5 t/ha decreased the pH slightly up to 5th day and then increased and equalled that of the control on the 90th day in all the soils. The decrease in pH was significantly more in the higher level of treatment then in the lower level. Water soluble iron increased significantly due to the treatments in all the soils. The maximum increase was observed in kari soil and the minimum in kayal and karappadom soils. However, the release of water soluble iron due to the higher level treatment was more than that of the lower level. The exchangeable iron also increased due to the organic matter treatment. The maximum increase was observed in the lateritic alluvium and the minimum in karappadom soils. The increase in the content of exchangeable iron due to higher level of organic matter was significantly higher than that due to the lower level. The lime application at full LR and half LR levels substantially increased the pH upto the 5th day in all the soils except in the kari soil, after which it decreased with further periods of submergence. However, in the kari soil, a peak value could be noticed on the 20th day. Water soluble and exchangeable iron decreased significantly due to the lime treatment. The decrease due to full LR treatment was significantly more than that due to the lower level. The active iron neither increased nor decreased significantly due to the organic matter and the lime treatments.